Differences between atrial and ventricular protein profiling in children with congenital heart disease - Pelouch, V; Milerová, M; Ostádal, B; Hucín, B; Samánek, M (Molecular and cellular biochemistry, 1995)
The purpose of the present study was to compare protein profiling of atria and ventricles in children operated for congenital heart disease. Tissue samples were obtained during surgery from patients with normoxemic (ventricular and atrial septal defects) and hypoxemic (tetralogy of Fallot) diseases. Protein fractions were isolated by stepwise extraction from both right ventricular and atrial musculature. The concentration of total atrial protein in the normoxemic patients exceeded the ventricular value (110 +/- 2.1 vs 99.9 +/- 4.0 mg.g-1 wet weight, respectively); in the hypoxemic group this atrio-ventricular difference disappeared. The concentration of contractile proteins in all cardiac samples was significantly higher in the ventricles as compared with atria, while the concentration of collagenous proteins was significantly higher in the atria (due to a higher amount of the insoluble collagenous fraction). The concentration of sarcoplasmic proteins (containing predominantly enzyme systems for aerobic and anaerobic substrate utilization), however did not differ between ventricles and atria. Furthermore, ventricular contractile fractions obtained from both normoxemic and hypoxemic patients were contaminated with the myosin light chain of atrial origin. Soluble collagenous fractions (containing newly synthesized collagenous proteins, predominantly collagen I and III), derived from all ventricular samples, were contaminated by low molecular weight fragments (mol. weight 29-35 kDa). The proportion of the soluble collagenous fraction was significantly higher in atrial but not in ventricular myocardium of hypoxemic children as compared with the normoxemic group. It seems, therefore, that lower oxygen saturation affects the synthesis of collagen preferentially in atrial tissue.
Keywords: frakcionace buněk; srdeční komory; proteiny; Male; Actins; Child, Preschool; Adolescent; Infant; Child; Hypoxia; dítě; Myosins; vrozené srdeční vady; kolagen; mužské pohlaví; elektroforéza v polyakrylamidovém gelu; aktiny; hydroxyprolin; mladiství; srdeční síně; Hydroxyproline; předškolní dítě; Electrophoresis, Polyacrylamide Gel; lidé; ženské pohlaví; Humans; Collagen; kojenec; Cell Fractionation; Heart Defects, Congenital; Heart Ventricles; Female; myosiny; Proteins; hypoxie; Heart Atria